«Отак тридцять літ тому було б вам зазирнути до Борислава…»: аналіз та інтерпретація оповідання І. Франка «Полуйка» - Дронь, К. (Слово і Час, 2021)
У статті здійснено аналіз-інтерпретацію Франкового оповідання «Полуйка», що ввійшло до другої тематичної збірки про нафтопромисловий Борислав — «“Полуйка” і інші бориславські оповідання» (Львів, 1899). З’ясовано походження, значення та індивідуально-авторське наповнен ня словоформи «полуйка», винесеної в заголовок. Розглянуто модерні, зокрема імпресіоністичні, принципи зображення робітничо-виробничого середовища крізь призму розповіді старого ріпника Івана, який на схилі життя згадує про робітничий звичай полуйки. Розкрито своєрідність сюжетно-композиційної побудови твору, скомпонованого на основі персонажної ретроспекції минулих подій. Досліджено низку новітніх змін на рівні формальних особливостей поетики. З огляду на дифузну генологічну сутність «Полуйки» (структура оповідання виявляє також виразні новелістичні аспекти) жанр твору потрактовано як новелізоване оповідання соціально-психологічного змісту. The paper analyzes the poetics of Ivan Franko’s story “Poluika” — the work that was included in the second thematic collection on the oil industry of Boryslav named “‘Poluika’ and other stories about Boryslav” (Lviv, 1899). The researcher focuses on the modern, in particular impressionistic, principles of displaying the working and industrial environment. The narration is performed through the life story of an old oilman who, being at the end of his life, recalls a custom of ‘poluika’, which existed among Boryslav oilmen thirty years ago. The new elements of “Poluika” poetics help in the deeper revealing of the inner world of a character, his values, and psychology. The story shows a number of new changes at the level of formal features of poetics. It presents still unknown aspects of Boryslav life and reflects the eloquent features of the modernistic type of I. Franko’s creative work. The story is based on retrospection of the events that happened thirty years ago, and this approach also makes its plot and composition peculiar. The origin, primary meaning, and expressive content of the word ‘poluika’, used as a title, have been clarified. The industrial landscape wasn’t new in contemporary literature but the writer tended to use it in an innovative way. The workers presented by Franko gain such new features as social, moral, and professional maturity. The researcher also pays attention to the peculiarities of applying the first-person form of narration tested by Ivan Franko in his works from 1870—1880. In general, “Poluika” has the genre features of a story but the structure of the work also reveals evident elements of a short story. Th us, the genre of “Poluika” is defined as a short story of social psychological content.